On the Complexity of Mechanisms and Consequences of Chromothripsis: An Update - Koltsova, Alla S.; Pendina, Anna A.; Efimova, Olga A.; Chiryaeva, Olga G.; Kuznetzova, Tatyana V.; Baranov, Vladislav S. (Frontiers in Genetics, 2019)
In the present review, we focus on the phenomenon of chromothripsis, a new type of complex chromosomal rearrangements. We discuss the challenges of chromothripsis detection and its distinction from other chromoanagenesis events. Along with already known causes and mechanisms, we introduce aberrant epigenetic regulation as a possible pathway to chromothripsis. We address the issue of chromothripsis characteristics in cancers and benign tumours, as well as chromothripsis inheritance in cases of its occurrence in germ cells, zygotes and early embryos. Summarising the presented data on different phenotypic effect of chromothripsis, we assume that its consequences are most likely determined not by the chromosome shattering and reassembly themselves, but by the genome regions involved in the rearrangement.